1998
DOI: 10.1097/00000542-199801000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Headache after Attempted Epidural Block 

Abstract: The use of air for loss-of-resistance testing during epidural block was associated with a higher incidence of PMPH, which might be attributable to subarachnoid air injection and CSF leakage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
1
9

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 10 publications
2
58
1
9
Order By: Relevance
“…We excluded women with PDPH symptoms lasting less than the first 24 hr after DP since these self-limiting headaches were likely to represent headache related to air used as part of loss of resistance technique rather than cerebral spinal fluid leak. 16 Women with recognized DP (meeting study entry criteria) but no evidence of PDPH stayed in hospital around the same amount of time as women with uncomplicated epidurals [33 ± 16 (SD) vs 35 ± 13 (SD) hours respectively]. We found that patients who developed PDPH stayed in hospital longer (17 hr on average), that the added time usually involved an extra overnight stay, and that both women with treated and untreated headache prior to discharge had a high rate of return to the ER for assessment and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded women with PDPH symptoms lasting less than the first 24 hr after DP since these self-limiting headaches were likely to represent headache related to air used as part of loss of resistance technique rather than cerebral spinal fluid leak. 16 Women with recognized DP (meeting study entry criteria) but no evidence of PDPH stayed in hospital around the same amount of time as women with uncomplicated epidurals [33 ± 16 (SD) vs 35 ± 13 (SD) hours respectively]. We found that patients who developed PDPH stayed in hospital longer (17 hr on average), that the added time usually involved an extra overnight stay, and that both women with treated and untreated headache prior to discharge had a high rate of return to the ER for assessment and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…By definition,pneumocephalus is a subarachnoid collection of air within the cranium, which is most commonly seen following intracranial neurosurgical procedures [10].Although rare,reports of pneumocephalus complicating administration of epidural labor analgesia have been published [1,2,5,6,7,8,13,16].Aide et al reported a significantly higher incidence of inadvertent dural puncture and subsequent development of headache in patients whose epidural block placement was accomplished with the LORA technique as opposed to the LORS technique [1]. The authors speculated that the incidence of pneumocephalus-related headache was directly related to the amount of air injected into the subarachnoid space [1].…”
Section: Discussionmentioning
confidence: 99%
“…The first mechanism involves the leakage of cerebrospinal fluid while the second mechanism involves intrathecal injection of air. [14] Because severe headache may be associated with pneumocephalus, at least 2 ml air in the subarachnoid area is sufficient. [15] In our case, we used 5 ml ozone.…”
Section: Discussionmentioning
confidence: 99%